High-Efficiency Production of Radiopharmaceuticals via Droplet Radiochemistry: A Review of Recent Progress. (9th December 2020) - Wang, Jia; van Dam, R. Michael
New platforms are enabling radiochemistry to be carried out in tiny, microliter-scale volumes, and this capability has enormous benefits for the production of radiopharmaceuticals. These droplet-based technologies can achieve comparable or better yields compared to conventional methods, but with vastly reduced reagent consumption, shorter synthesis time, higher molar activity (even for low activity batches), faster purification, and ultra-compact system size. We review here the state of the art of this emerging direction, summarize the radiotracers and prosthetic groups that have been synthesized in droplet format, describe recent achievements in scaling up activity levels, and discuss advantages and limitations and the future outlook of these innovative devices.